Construction of Public Opinion in Web 2.0 - Chauca Amado, Lorena (2012)
Web 2.0 has become an important space for citizens to get together and spread their complaints on matters of public interest. In Peru, we can see this in citizen campaigns that are organized on the Internet. In 2007, the most important campaign was “Adopt a congressman”, that demanded Peruvian legislators to show their operating expenses. Another known case is “D’onofrio, far from you”, a protest against the ice-cream factory D’onofrio that took place on Facebook, Twitter and blogs. The protest was motivated by a promotion that said the factory was going to sell all of its ice creams for one sol for acouple of days. However, people had trouble finding ice cream men those days, and most of them just sold only the products that usually cost one sol.